(untitled) (New York, 1994)
Computing as a human enterprise; computers and problem solving; Logic and problem solving; Problem breakdown and abstraction; Coding and presentation; Logic and program correctness; Logic and computers...
Keywords: Xử lý dữ liệu điện tử,Electronic data processing